Apple powdery mildew caused by Podosphaera leucotricha: some aspects of disease management - Holb, I. J. (International Journal of Horticultural Science, 2014)
Apple powdery mildew (Podoshphaera leucorticha) occurs wherever apples are grown. One of the most important fungal disease of apple which causing severe econimic loss on susceptible apple cultivars. This review focuses on the control of apple powdery mildew. The first part of the study provides details of novel aspects of non-chemical control approaches, including agronomic measures, mechanical and biological control options as well as essential features of apple cultivar resistance. After this, developments in chemical control options are described sperately for integrated and organic apple orchards.